PEMBELAJARAN MUFRODAT DENGAN METODE BERNYANYI DALAM MENGHAFAL KOSAKATA DI MADRASAH IBTIDAIYYAH AL KHAIRIYAH - Najwa Huzaifah; Hikmah Maulani (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
Learning mufrodat (vocabulary) is one of the important aspects in learning Arabic. One of the effective methods to improve the ability to memorize vocabulary is through singing. This study aims to examine the effectiveness of singing method in mufrodat learning, especially in helping students memorize vocabulary in a fun and sustainable way. This method utilizes simple melodies that are adapted to the theme of the vocabulary being learned, so as to attract students' interest and strengthen memory. The study used a qualitative approach with data collection through observation, interviews, and learning outcome tests. The results showed that the singing method not only improved students' ability to memorize mufrodat, but also created a more interactive and fun learning atmosphere. Thus, the singing method can be an innovative alternative in Arabic language learning that is oriented towards vocabulary mastery.